TEACHING ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA: THE ROLE OF SCHOOL ENVIRONMENT - Djoko Susanto (University of Muhammadiyah Purwokerto, 2013)
This paper examines the important role of the school environments to facilitate English program in Indonesian primary schools. The school environment here refers to the environment inside the school: principal, teachers, and foreign language (FL) classroom; and outside the school: the students’ parents and the school community. Researchers have investigated teaching English as foreign language (TEFL) in primary schools from different perspectives, such as curriculum, teacher’s role, and materials; however, little attention is paid to examine school environment as an important factor to improve the quality of TEFL in Indonesia. The data is taken from the results of my Masters study investigating the implementation of Indonesian language as LOTE program in Kingsbury Primary School (KPS), Bundoora, Melbourne, Australia. Interviews, questionnaires, and observations were employed to obtain the answers as to why Indonesian language was selected as the LOTE program in KPS. The study found several factors supporting the program, and one of the findings relevant to this present investigation was the positive attitude given by the environments. The main reason why Indonesian language was taken as the LOTE program was because there were many Indonesian people who lived around the school and frequently involved in the school activities. This was believed by the school council as important linguistic evidence to establish the program. All the members of the school environment were very supportive. The non-LOTE teachers, for example, occasionally attended the course and watched their children learning Indonesian language. The purpose of doing that, according to the non-LOTE teachers, was to motivate their children to learn it seriously as the children also saw their teachers came and learnt it. The LOTE program was also made possible by the availability of a representative classroom which was fairly large for doing class activities. This classroom was designed especially for the LOTE program and it was completed with printed materials such as books, comics, posters, short stories, and audio visual aids to show the Indonesian family, life and culture. The principal, the LOTE teacher, and LOTE coordinator claimed that having such particular classroom was significant to build the students’ motivation to practice the target language when coming into the LOTE classroom because they were immersed with the atmosphere inside the room in which they could read anything written in Indonesian language. Keywords: language, literature, pedagogical approaches, non-native learners.